Українські політичні реалії в англомовному політичному дискурсі - Нарійчук, Марія Федорівна; Nariychuk, M. F. (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті розглядаються особливості трансляції українських реалій в англомовний політичний дискурс. Уперше здійснено спробу комплексного вивчення української суспільно-політичної лексики в аспекті її вжи¬вання та застосування в сучасній англійській мові. Дослідження виконано на матеріалі суспільно-політичної онлайн-газети «KyivPost» (суспільно-політичний тижневик, одне з провідних англомовних видань України), онлайн-сторінок незалежних неурядових організацій «Національний демократичний інститут» (The National Democratic Institute), «Міжнародний республіканський інститут» (The International Republican Institute), ОБСЄ (OSCE). The article features the transmission of Ukrainian political realia into English political discourse. This research presents the first comprehensive study of Ukrainian socio-political vocabulary in terms of its use and application in the modern English language. The study was performed on the material of socio-political online newspaper «KyivPost» (newsweekly, one of the leading English-language newspapers in Ukraine), the online pages of NGOs «The National Democratic Institute», «The International Republican Institute», the OSCE. The selected vocabulary is presented in the following thematic groups: names of political parties, blocs, NGOs; vocabulary related to Ukrainian governmental system; vocabulary representing ideology; the names of cities, regions and urban centers; vocabulary related to the socio-technical sphere.
Ukrainian Political Realia in English Political Discourse
Keywords: політичний дискурс; political discourse; суспільно-політична лексика; socio-political vocabulary; реалії; realia